(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Yulia G. Gorpennikova (Southern Federal University, Rostov-on-Don, Russian Federation) The real research is fulfilled in the actual communicative and pragmatical direction. We have generalized data of the earlier conducted researches, and have expanded the existing notions about the specific features of the communicative tactics used in the strategy of apology. The apology is understood as mitigative communicative strategy, which is structured by means of certain complex of business communications signs. A range of communicative tactics and its specific language means construct the phenomenon of apology in the process of speech. The article examines Language units of the revealed tactics. Keywords: apology, communicative strategy, business communication, tactic, ritual statement, mitigation. DOI 10.23683/1995-0640-2017-2-107-117